THE IMPACT OF CONVERTING THE FUNCTION OF AGRICULTURAL LAND INTO SETTLEMENTS ON FARMERS' INCOME IN GAMPONG PADANG, MANGGENG DISTRICT, SOUTHWEST ACEH DISTRICT - Baihaqi; Rusdi Faizin (RADJA PUBLIKA, 2023)
This research was conducted to see how much impact the conversion of agricultural land into residential areas had on farmers' income in Gampong Padang, Manggeng District, Southwest Aceh Regency. The research was conducted in Padang Village, Manggeng District, Southwest Aceh Regency. This research was carried out in October-November 2022. In this research the type of data used is data (descriptive) while the data sources used are primary data sources and secondary data. The data analysis technique used is descriptive qualitative, namely the data obtained and collected is then studied and presented in tabular form. The results of the research show that the impact of agricultural land conversion in Padang village is negative, where farmers' income after land conversion decreases up to two times compared to before land conversion.